2003
DOI: 10.1017/s002211200300627x
|View full text |Cite
|
Sign up to set email alerts
|

On the low-Reynolds-number flow about two rotating circular cylinders

Abstract: International audienceThe viscous and steady flow about two distinct parallel infinite rotating circular cylinders is theoretically investigated. Because any inner steady Stokes flow is not quiescent far from the cylinders, a strictly steady analysis requires matching an inner steady Stokes approximation with an outer solution of the steady Navier-Stokes equations. However, except for the case of identical cylinders of equal angular velocities, it is impossible to determine this outer solution. In the same spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…9 Since then, several authors have presented extensive analytical studies for the behaviour of the flow at low Reynolds numbers. 10,11 Numerical results for the flow past a fixed counter-rotating cylinder pair at non-zero Reynolds numbers were presented by Chan et al 12 They found that for certain combinations of inflow and rotational velocities, the vortical wake was suppressed resulting in zero or negative drag values. In the context of self-propulsion, steady-state solutions were found numerically for two counter-rotating cylinders 13,14 and an axisymmetric torus.…”
Section: Introductionmentioning
confidence: 99%
“…9 Since then, several authors have presented extensive analytical studies for the behaviour of the flow at low Reynolds numbers. 10,11 Numerical results for the flow past a fixed counter-rotating cylinder pair at non-zero Reynolds numbers were presented by Chan et al 12 They found that for certain combinations of inflow and rotational velocities, the vortical wake was suppressed resulting in zero or negative drag values. In the context of self-propulsion, steady-state solutions were found numerically for two counter-rotating cylinders 13,14 and an axisymmetric torus.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the investigation, however, has remained mainly theoretical and mathematical. 3,4 With current Computational Fluid Dynamic capability, the characteristics of this special flow can certainly be more fully quantified numerically by solving the full governing equations with a high-order accurate scheme, hence the motivation of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Micropumps based on this principle have been studied experimentally [48] and numerically [20,21]. Moreover, pairs of corotating cylinders in an unbounded viscous fluid mutually exert forces on each other that are perpendicular to their connecting line at leading-order of approximation [49], causing the pairs to circulate about each other.…”
Section: A Linear Channels With Freely Moving Colloidsmentioning
confidence: 99%